Some of Ibn Taymiyyah's Opinions on Syntax: the Abrogators of the Nominal Sentence - Habal, Khireddine (Milev Journal of Research and Studies, 2018)
This article highlights some of the grammatical aspects that Shaykh alIslam Ibn Taymiyah referred to in his book Fatwas, which clearly shows his ability to reach the point of the Arabic grammar. In this paper he reviews the views of Ibn Taymiyya in the chapter on the nouns. The views of the plaques signify the firmness of his foot in Arabic grammar.